Seismic vulnerability analysis of the irregular RC building with transfer beam under near field earthquake with vertical component - Farhanah Afiqah Binti Razman (School of Environmental Engineering, University Malaysia Perlis, 2014)
This study represent an educate analysis of seismic activity of vertical component to observe and study the pattern of response of the building toward the vertical component ground motion. Four frame structure were design where two difference practice of design that is earthquake design and gravity design practice and each practice contain two type of design that is regular RC building and irregular RC building and 10 ground motion were selected.